2020
DOI: 10.1155/2020/3158954
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Its Relationship with Coping Strategies and Illness Perceptions during the COVID-19 Lockdown in Greece: A Cross-Sectional Survey of the Population

Abstract: Objective. The COVID-19 epidemic has shown a more benign course in Greece possibly due to the early lockdown measures. Mental health consequences of the lockdown however are unknown. In addition, illness perceptions and relevant strategies to cope with the stress of the epidemic may have played a role in complying with the restrictions. We conducted a survey of the Greek population with the aim to investigate the prevalence of anxiety and depression during the lockdown, the emotional impact of the epidemic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
111
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 51 publications
14
111
1
3
Order By: Relevance
“…Interventions that decrease the use of maladaptive coping style can also reduce long-term distress ( 48 ). However, poor mental health status influences the approaches of coping strategy which could result in a negative effect ( 49 ). Social support, as an important coping resource, contributes to developing individual resilience and effective coping skills in adverse circumstances ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that decrease the use of maladaptive coping style can also reduce long-term distress ( 48 ). However, poor mental health status influences the approaches of coping strategy which could result in a negative effect ( 49 ). Social support, as an important coping resource, contributes to developing individual resilience and effective coping skills in adverse circumstances ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Validated versions of the tests in the various languages spoken in the seven countries were employed. Moreover, considering previous researches performed on a one-country level, IES-R and DASS-21 were used during COVID-19 research in China ( Hao et al., 2020 ), India ( Chew et al., 2020 ), Vietnam ( Le et al., 2020 ), Singapore ( Tan et al., 2020 ), and Philippines ( Tee et al., 2020 ); MASS was adopted in Italy ( Conversano et al., 2020 ; Baiano et al., 2020 ) and Brazil (Kozasa et al., 2020); PSS10 was used in Brazil (Kozasa et al., 2020), China ( Duan et al., 2020 ; Yan et al., 2020 ) and Colombia ( Pedrozo-Pupo et al., 2020 ); PHQ9 was employed in Greece ( Skapinakis et al., 2020 ), Italy ( Rapisarda et al., 2020 ), Spain ( Garre-Olmo et al., 2021 ) and China ( Yao, 2020 ); Brief-COPE was used in Australia ( Gurvich et al., 2020 ), Greece ( Skapinakis et al., 2020 ), United Kingdom ( Dawson and Golijani-Moghaddam, 2020 ) and USA ( Umucu and Lee, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…One in China indicated that during the pandemic the mental health of female health care workers took a substantial toll, with them being far more anxious than men [ 18 , 19 ]. While other research supported the idea that females had lower mental well-being scores throughout the pandemic [ 20 , 21 ].…”
Section: Main Textmentioning
confidence: 99%